Heterotaxy polysplenia syndrome with cholangiopancreatic cancer: a case report and literature review - Chen, Ziye; Chen, Yu-Ann; Wang, Xuedong; Song, Wenyan; Geng, Yadi; Wang, Pengfei; Kong, Siming; Dong, Jiahong; Bai, Hui; Wang, Yunfang (Frontiers in Medicine, 2025)
BackgroundHeterotaxy polysplenia syndrome is a rare condition characterized by multiple abnormal spleens and irregular placement of various organs. Some patients have been documented as developing various types of cancers, although the association with heterotaxy polysplenia syndrome remains uncertain. Most cases of heterotaxy polysplenia syndrome are isolated anomalies, but there are rare instances where it appears in closely related individuals, suggesting possible genetic inheritance.Case presentationWe report the case of a 36-year-old woman with heterotaxy polysplenia syndrome, who presented with choledocholithiasis, thickening and stenosis of the hepatic portal bile duct wall, duodenal atresia, and congenital pancreatic insufficiency. Following recovery from a COVID-19 infection, the patient incidentally identified a mass in the upper abdomen. Pathological examination revealed the mass to be a poorly differentiated adenocarcinoma of pancreaticobiliary origin. Additionally, a familial pattern of situs inversus and breast cancer was observed. In this report, we also provide a comprehensive literature review to enhance the understanding of heterotaxy polysplenia syndrome and to explore the potential association between this condition and tumor development.ConclusionOur report contributes to the current knowledge about heterotaxy polysplenia syndrome and its potential association with tumors. Effective integration of clinical diagnostic information, exploration of precise means of diagnosing and treating rare diseases, and incorporation of the patient's familial background are promising for future research and clinical interventions.